Ebosin Ameliorates Psoriasis-Like Inflammation of Mice via miR-155 Targeting tnfaip3 on IL-17 Pathway - Guo, Weiwei; Xu, Fengying; Zhuang, Zhuochen; Liu, Zhe; Xie, Jiming; Bai, Liping (Frontiers in Immunology, 2021)
Psoriasis is a recurrent autoimmune skin disease with aberrant regulation of keratinocytes and immunocytes. There is no available cure for psoriasis, and the establishment of a treatment option to control its signs and symptoms is urgently needed. Here, we found Ebosin, a novel exopolysaccharide isolated from Streptomyces sp. 139 by our lab, not only could ameliorate inflammation in LPS-induced keratinocytes through IKK/NF-kapaB pathway, but also attenuate psoriatic skin lesions and reduce inflammatory factors expression in imiquimod (IMQ)-mediated psoriatic mice. Except for inhibiting the expression of epidermal differentiation related proteins, Ebosin significantly increased the percentage of CD4+Foxp3+CD25+ Tregs and decreased CD4+IL17A+ Th17 cells in psoriatic mice. Furthermore, we demonstrate that Ebosin significantly suppressed the IL-17 signaling pathway via A20 (encoded by tnfaip3) in vivo. As the direct binding of tnfaip3 to miR-155 has been demonstrated by luciferase reporter assay, and Ebosin has been demonstrated to inhibit miR-155 level in vitro and in vivo, our study first indicates that Ebosin reduces inflammation through the miR-155-tnfaip3-IL-17 axis and T cell differentiation in a psoriasis-like model. Thus we conclude that Ebosin can act as a promising therapeutic candidate for the treatment of psoriasis.